(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
Catharanthus roseus or “Kemunting Cina” and Clitoria ternatea or “Bunga Telang" had a long reputation as a traditional remedy in South East Asia. One of the important components that contribute to these plants’ remedial capabilities is the secondary metabolic known as phenolic. In this study, the Total Phenolic Contents or TPC in Catharanthus roseus and Clitoria ternatea leaves extract have been obtained and compared. Leaves from both species were dried and the extract was acquired using 90% ethanol via a rotary evaporator. Two major tests were conducted which are the qualitative test and quantitative test. The qualitative test was done to ensure the existence of phenolic in the samples. Meanwhile, the quantitative test is to measure the concentration of phenolic in the samples. Both samples show a positive result in a qualitative test where the extract of the sample changed from green to dark green in the Ferric Chloride test. Next, Folin- Ciocalteu assay acted as the quantitative test to determine the TPC in the samples, and the absorbance was measured at 760 nm. The test was triplicated to ensure the consistency of the results. The total phenolic content for Catharanthus roseus is 36.33600 ± 0.935313mg/GAE and Clitoria ternatea is 7.35767 ± 0.046188mg/GAE. The TPC in Catharanthus roseus is higher than Clitoria ternatea. The t-test shows that there is a significant difference in concentration of total phenolic content between Catharanthus roseus and Clitoria ternatea (p